Epigenetic Silencing of TAP1 in Aldefluor+ Breast Cancer Stem Cells Contributes to Their Enhanced Immune Evasion. (30th January 2018) - Sultan, Mohammad; Vidovic, Dejan; Paine, Arianne S.; Huynh, Thomas T.; Coyle, Krysta M.; Thomas, Margaret L.; Cruickshank, Brianne M.; Dean, Cheryl A.; Clements, Derek R.; Kim, Youra; Lee, Kristen; Gujar, Shashi A.; et al.
Abstract : Avoiding detection and destruction by immune cells is key for tumor initiation and progression. The important role of cancer stem cells (CSCs) in tumor initiation has been well established, yet their ability to evade immune detection and targeting is only partly understood. To investigate the ability of breast CSCs to evade immune detection, we identified a highly tumorigenic population in a spontaneous murine mammary tumor based on increased aldehyde dehydrogenase activity. We performed tumor growth studies in immunocompetent and immunocompromised mice. In immunocompetent mice, growth of the spontaneous mammary tumor was restricted; however, the Aldefluor + population was expanded, suggesting inherent resistance mechanisms. Gene expression analysis of the sorted tumor cells revealed that the Aldefluor + tumor cells has decreased expression of transporter associated with antigen processing (TAP) genes and co-stimulatory molecule CD80, which would decrease susceptibility to T cells. Similarly, the Aldefluor + population of patient tumors and 4T1 murine mammary cells had decreased expression of TAP and co-stimulatory molecule genes. In contrast, breast CSCs identified by CD44 + CD24 − do not have decreased expression of these genes, but do have increased expression of C-X-C chemokine receptor type 4. Decitabine treatment and bisulfite pyrosequencing suggests that DNA hypermethylation contributes to decreased TAP gene expression in Aldefluor + CSCs. TAP1 knockdown resulted in increased tumor growth of 4T1 cells in immunocompetent mice. Together, this suggests immune evasion mechanisms in breast CSCs are marker specific and epigenetic silencing of TAP1 in Aldefluor + breast CSCs contributes to their enhanced survival under immune pressure. Abstract : Growth of a spontaneous murine mammary was restricted in immunocompetent mice; however, the Aldefluor + tumorigenic population was expanded, suggesting inherent resistance mechanisms to immune pressure in these cells. Gene expression analysis of the sorted tumor cells revealed that the Aldefluor + tumor cells have decreased expression of transporter associated with antigen processing 1 (TAP1). Similarly, the Aldefluor + population of patient tumors and 4T1 murine mammary cells had decreased expression of TAP1. Decitabine treatment and bisulfite pyrosequencing suggests that DNA hypermethylation contributes to decreased TAP1 expression in Aldefluor + cancer stem cells (CSCs). Together, this suggests epigenetic silencing of TAP1 in Aldefluor + breast CSCs contributes to their enhanced survival under immune pressure.